Factors Affecting Writing Skill Using Computer Assisted Test (CAT) in Junior High School Students - Suhita, Raheni; J. Waluyo, Herman; Setiawan, Budhi (International Journal of Engineering and Technology, 2018)
This study aimed to determine the factors affecting writing skill quality and the level of their contribution to help language teachers to formulate more effective strategies using CAT to enhance writing skill. The correlating factors discussed in this research were studentsâ€™ reading comprehension skill, vocabulary mastery, and attitude toward language.Â The study applied quantitative approach with simple and multiple correlation and regression techniques. The samples of the study were 100 students taken using stratified random sampling technique from a population of 2000 junior high school students in Surakarta City. The data were collected using multiple choice test for studentsâ€™ reading comprehension skills and vocabulary mastery, writing assignments, and questionnaires for their attitudes toward the Indonesian language. The findings showed that there are positive correlations between the independent variables, either individually or simultaneously, with writing skill. The individual contribution levels is 44.75% of reading comprehension skill, 27.70% of vocabulary mastery, and 28.5% of attitude toward language. As for the simultaneous correlation of the three determining factors make up to 45.16%. contribution level to writing skill quality. Thus it can be concluded that reading comprehension has the most contribution to writing skill compared to vocabulary mastery and attitude toward language. The identified levels of contribution can be taken into consideration in formulating teaching strategies and materials to enhance writing skill quality.Â Â